2020
DOI: 10.1111/1346-8138.15487
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic clues of palmoplantar hyperkeratotic eczema and palmoplantar psoriasis: A prospective, comparative study of 90 patients

Abstract: Diagnosis can be difficult in isolated palmar and plantar lesions in patients with psoriasis and eczema. The purpose of our study is to compare the dermoscopic findings in patients with palmoplantar psoriasis and palmoplantar hyperkeratotic eczema. This prospective, comparative study included 90 patients histopathologically diagnosed with eczema or psoriasis (35 psoriasis and 55 eczema). The age range was 18-75 years. The most common vessel type was dot vessel in psoriasis. Red globular ring vessels were seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
24
3
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 29 publications
16
24
3
4
Order By: Relevance
“…Although dotted vessels are a hallmark of trunk and extremity plaque psoriasis [6], as well as palmoplantar involvement [2], it should be remarked that this finding is not specific for psoriasis vulgaris. It could also be seen in eczema [2,3], Bowen's disease [7], lichen nitidus [8], lichen simplex chronicus [15] and PRP [5,9,16].…”
Section: Psoriasis Vulgarismentioning
confidence: 94%
See 4 more Smart Citations
“…Although dotted vessels are a hallmark of trunk and extremity plaque psoriasis [6], as well as palmoplantar involvement [2], it should be remarked that this finding is not specific for psoriasis vulgaris. It could also be seen in eczema [2,3], Bowen's disease [7], lichen nitidus [8], lichen simplex chronicus [15] and PRP [5,9,16].…”
Section: Psoriasis Vulgarismentioning
confidence: 94%
“…Although dotted vessels are a hallmark of trunk and extremity plaque psoriasis [6], as well as palmoplantar involvement [2], it should be remarked that this finding is not specific for psoriasis vulgaris. It could also be seen in eczema [2,3], Bowen's disease [7], lichen nitidus [8], lichen simplex chronicus [15] and PRP [5,9,16]. Based on these findings, it can be suggested that dotted vessels may not be useful to distinguish psoriasis from other dermatoses, but the vascular distribution pattern may be beneficial in the differential diagnosis [2,3,17,18].…”
Section: Psoriasis Vulgarismentioning
confidence: 94%
See 3 more Smart Citations